1988
DOI: 10.1007/bf00582541
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ADH on sodium, chloride, potassium, calcium and magnesium transport in cortical and medullary thick ascending limbs of mouse nephron

Abstract: The effect of antidiuretic hormone (arginine vasopressin, AVP) on transepithelial Na+, Cl-, K+, Ca2+ and Mg2+ net transports was investigated in medullary (mTAL) and cortical (cTAL) segments of the thick ascending limb (TAL) of mouse nephron, perfused in vitro. Transepithelial net fluxes (JNa+, JCl-, JK+, JCa2+, JMg2+) were determined by electron probe analysis of the collected tubular fluid. Transepithelial potential difference (PDte) and transepithelial resistance (Rte) were measured simultaneously. cTAL seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…Interestingly, one study showed that the presence of bicarbonate enhances the mTAL Ca 2ϩ flux (42), whereas most perfusion studies are performed in the absence of HCO 3 Ϫ . Based on flux measurements, we assumed here that the mTAL permeability to Ca 2ϩ is one tenth that of the cTAL.…”
Section: Calcium Reabsorption In the Talmentioning
confidence: 99%
“…Interestingly, one study showed that the presence of bicarbonate enhances the mTAL Ca 2ϩ flux (42), whereas most perfusion studies are performed in the absence of HCO 3 Ϫ . Based on flux measurements, we assumed here that the mTAL permeability to Ca 2ϩ is one tenth that of the cTAL.…”
Section: Calcium Reabsorption In the Talmentioning
confidence: 99%
“…More importantly, the short term effects of vasopressin on TAL electrolyte transport were demonstrated in early studies in isolated microperfused tubules. Addition of vasopressin to the bath stimulates cAMP production (11,12) and transepithelial bumetanide-sensitive chloride fluxes (13)(14)(15)(16). These effects of vasopressin are more pronounced in rodents, whereas they are weak or absent in species with a lesser urinary concentrating ability (17).…”
mentioning
confidence: 99%
“…22 Briefly, the dissected tubules, 0.3 to 0.5 mm in length, were mounted on a set of concentric micropipettes and perfused at 37°C at rates of 2 to 3 nL/min. Asymmetrical conditions of osmolality and sodium concentration for bathing and perfused solutions were chosen 23,18 to maximize water flux and to study precisely both the sodium and water movements.…”
Section: Measurement Of Water and Sodium Transport In Isolated Perfusmentioning
confidence: 99%